1982
DOI: 10.1111/j.1365-2125.1982.tb04941.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of clonidine induced miosis by the alpha 2‐adrenoreceptor antagonist RX 781094.

Abstract: Clonidine given i.v. at a dose of 0.1 mg and 0.2 mg was found to cause miosis in a placebo controlled double‐blind study in six healthy volunteers. In a further single‐blind placebo controlled study in three of these volunteers, the alpha 2‐adrenoreceptor antagonist RX 781094 at a dose of 0.1 mg/kg i.v. reversed the miosis induced by i.v. clonidine 0.2 mg. At a dose of 0.05 mg/kg the miosis was partially reversed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 4 publications
0
15
2
Order By: Relevance
“…However, a miotic effect of clonidine has been described when pupil diameter is measured in an illuminated environment (Clifford et al 1982(Clifford et al , 1989Fanciullacci et al 1988;Bitsios et al 1996Bitsios et al , 1998. On the other hand, yohimbine increased resting pupil diameter, both in the present study and the earlier experiment of Morley et al (1991).…”
Section: Discussioncontrasting
confidence: 47%
“…However, a miotic effect of clonidine has been described when pupil diameter is measured in an illuminated environment (Clifford et al 1982(Clifford et al , 1989Fanciullacci et al 1988;Bitsios et al 1996Bitsios et al , 1998. On the other hand, yohimbine increased resting pupil diameter, both in the present study and the earlier experiment of Morley et al (1991).…”
Section: Discussioncontrasting
confidence: 47%
“…Although a quantitative relationship between the level of illumination and the size of the miotic response to clonidine has not been demonstrated previously, the present results are in good qualitative agreement with previous reports in the literature. Firstly, the effect of clonidine on the pupil in the dark has been reported to be either nonobservable [6], or very small [4], and most reports of a miotic effect of clonidine are based on experiments conducted in an illuminated room [1–3]. Secondly, it has been reported that the size of the miotic response to clonidine in the same group of subjects is larger when the measurement is carried out under illumination rather than in the dark [4].…”
Section: Discussionmentioning
confidence: 99%
“…In humans the systemic administration of the α 2 ‐adrenoceptor agonist clonidine evokes a miotic response [1–5], whilst administration of the α 2 ‐adrenoceptor antagonist yohimbine evokes mydriasis [6]. Furthermore, the clonidine‐evoked miosis is susceptible to antagonism by α 2 ‐adrenoceptor antagonists [1, 3]. In a recent study Bitsios et al.…”
Section: Introductionmentioning
confidence: 99%
“…In human, there is reduction in gastrointestinal motility, sedation, inhibition of the micturition reflex, and miosis (Clifford et al, 1982). In rodent, some of them are the same reaction, but some are different from human.…”
mentioning
confidence: 99%